Spór o uniwersalia - Jaroszewska, Anna (Filozofia Publiczna i Edukacja Demokratyczna, 2012)
The problem of universals has been taken over by the medieval philosophers through the commentators, especially by Porfiriusz. Medieval philosophers had united issues mentioned by Porfiriusz with response to Boecjusz, creating an alternative: “thing” or “ word”. The most staunch phase of the dispute took place in the XI and XII centuries around two positions: “a realistic” and “nominalistic”, there has been an attempt to reach a compromise by marginal discarding; then three concepts was developed: “conceptualism” (“sermonizm”), “moderate conceptual realism” or “set theory”.